A DFT-chemotopological study on the 3D transition metal oxides anddioxygen complexes (2016)
Density functional theory unrestricted calculations at the BPW91/6-311+G* level of theory have been usedto explore the potential energy surface of MOncomplexes (M = Sc–Zn, n = 1–2). Nine physico-chemicalproperties were selected to characterize each of the MOncomplexes to conduct a chemotopologicalstudy. Our results show that the similarity relations between the group-VIIIB elements (Fe, Co and Ni)are transferred to their corresponding MOncomplexes. A classification of M O interactions in the MOncomplexes based on the QTAIM methodology is introduced.